ALL YOU CAN EAT PRACTICE IN MODERN CONSUMER CULTURE: LAW IN ISLAM - Khairi, Muhammad Fakhri; Azzaki , Muhammad Adnan (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The rapid development of the culinary business can be seen from the many modifications and marketing strategies aimed at increasing consumer interest. One of the marketing strategies that has attracted a lot of attention and is increasingly developing in Indonesia is the practice of eating as much as you can or commonly known as